УКРАЇНСЬКИЙ МУЗИЧНИЙ ФОЛЬКЛОР ЯК ЗАСІБ ЕМОЦІЙНОГО ВИХОВАННЯ УЧНІВ МОЛОДШИХ КЛАСІВ (Педагогіка вищої та середньої школи, 2022)
In the article it is distinguished the active forms of work with the material of Ukrainian musical folklore; which promote the education process possibilities with decision of the problem in emotional education of junior pupils.